New survey evidence on the pricing behaviour of Luxembourg firms - Patrick Lünnemann; Thomas Y. Mathä (European Central Bank (ECB), 2006)
This paper analyses the pricing behaviour of Luxembourg firms based on survey evidence. Luxembourg firms typically have low market share, many competitors and longstanding customer relationships. Price discrimination is frequently applied. A majority of firms use price review rules that include elements of state dependency. The median firm reviews and changes prices twice a year. The results suggest an almost equal share of firms applying forwardlooking, backward-looking and rules of thumb behaviour. The adjustment speed is faster when cost goes up and demand goes down than in the opposite cases. The most relevant theories explaining price rigidity are implicit contracts, cost-based pricing and explicit contracts. Increases in labour and other costs are the most important factors leading to price increases; for price reductions it is price reductions by competitors followed by declining labour costs.
Keywords: C21; C22; C14; 330; adjustment speed; price rigidity; price setting; survey data; Preismanagement; Preisrigidität; Luxemburg